Nutritional and clinical profile of women with polycystic ovary syndrome - Luz, Beatriz Coelho da; Martins, Paloma Esthefany Bezerra; Silva, Amanda Alves Marcelino da; Cavalcante, Taisy Cinthia Ferro; Tomiya, Marília Tokiko Oliveira; Souza, Thays Kallyne Marinho de (Seven Editora, 2023)
Polycystic ovary syndrome (PCOS) is a complex endocrine disease with heterogeneous clinical signs and symptoms, its main manifestations and clinical consequences being hyperandrogenism, and chronic anovulation, irregular menstrual cycles, presence of multiple cysts in the ovaries and decreased implantation potential embryonic. The aim of this study was to characterize the nutritional and clinical profile of women with Polycystic Ovary Syndrome. The study was carried out virtually using Google Forms from the Google platform, in which the link was made available on social networks. The form contained questions about sociodemographic information, symptoms related to PCOS, presence or absence of chronic noncommunicable diseases, anthropometric data and food consumption using a Food Frequency Questionnaire (FFQ). The participants were 41 women with a mean age of 23.83 ± 4.77 years, with a mean weight, height, BMI and waist circumference of 69.56 ± 17.21 Kg; 1.61 ± 0.06 m; 26.86 ± 7.13 kg/m²; 80.22 ± 12.62 cm; respectively. Most women had depression/anxiety (60.98%) and were overweight/obese (56.10%). The most reported PCOS symptom was menstrual dysfunction (90.24%). There was no statistical significance between the foods consumed and the symptomatology of PCOS (p>0.05). From this study, it is concluded that women with PCOS have a prevalence of overweight and depression and/or anxiety, also showing that the nutritional diagnosis based on the assessment of nutritional status and food consumption is of paramount importance to guide intervention strategies for treating PCOS such as changing lifestyle and eating habits. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-144